Cooperative Integrated Reading And Composition (Circ) Strategy In Teaching Writing Descriptive Text - Fauziah, Elisah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2020)
Writing is one of the four basic English skills. In teaching writing, the teacher finds strategies or media which help students easy to write a text. The researcher using Cooperative Integrated Reading and Composition (CIRC) strategy to teaching writing descriptive text. This study aims to determine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) strategy in teaching writing descriptive text in Senior High School. In this research, the researcher uses a quasi-experimental design. The population of this research is tenth graders students of MA Al-IhsanKalijaring in X-IPA class as the experimental group is taught by using Cooperative Integrated Reading and Composition (CIRC) Strategy. Furthermore, the class was the control group by using conventional learning. It used the test writing and scoring rubric as the instruments to score the test. Since the assumption of normality, the researchers analyze the data using Mann-Whitney Test. The result of this research has shown the significant value of Asymp. Sig. (2-tailed) was higher than significant level (0.665 > 0,05). It means that (Ho) was accepted while (Ha) was rejected. Based on the result of this study, the researcher concludes that Cooperative Integrated Reading and Composition (CIRC) strategy was not effective in teaching writing descriptive text to tenth graders students.